Somatosensory Stimulus Intensity Encoding in Borderline Personality Disorder - Malejko, Kathrin; Neff, Dominik; Brown, Rebecca C.; Plener, Paul L.; Bonenberger, Martina; Abler, Birgit; Grön, Georg; Graf, Heiko (Frontiers in Psychology, 2018)
Borderline Personality Disorder (BPD) is clinically characterized by emotional instability, interpersonal disturbances and dysfunctional behavior such as non-suicidal self-injury (NSSI). During NSSI, patients with BPD typically report analgesic or hypoalgesic phenomena, and pain perception and pain processing in BPD have been repeatedly investigated. Most of the studies so far focused on affective-motivational and cognitive-evaluative neural components of pain within categorial study designs. By contrast, rather basic somatosensory aspects such as neural intensity-encoding of somatosensory stimuli were not examined in further details. Thus, we investigated patients with BPD and healthy controls (HC) by functional magnetic resonance imaging (fMRI) during an unpleasant sensory stimulation task with parametrically increasing stimulus intensities. 15 females diagnosed with BPD and 15 HCs were investigated with fMRI during four individually adjusted levels of electrical stimulus intensities. Ratings of stimulus intensity were assessed by button presses during fMRI. fMRI-data were analyzed by analyses of variances (ANOVA) at a statistical threshold of p<0.05 FWE-corrected on cluster level. Subjective ratings of stimulus intensities were alike between BPD and HC, and intensity levels identified with equal accuracy. Significant intensity-encoding neural activations were observed within the primary and secondary somtasensory cortex, the posterior insula, the posterior midcingulate cortex (pMCC) and the supplementary motor area (SMA) in both, HC and BPD. Notably, there were no significant between-groups differences in intensity-encoding neural activations, even at lowered significance thresholds. Present results suggest a similar neural somatosensory stimulus intensity encoding in BPD as previously observed on a behavioral level. The alterations in neural affective-motivational or cognitive-evaluative components reported so far may be restricted to pain rather than unpleasant stimulus processing and were absent in our study.